Madagascar Influence on the South Indian Ocean Convergence Zone, the Mozambique Channel Trough and Southern African Rainfall. Issue 20 (27th October 2018) - Barimalala, Rondrotiana; Desbiolles, Fabien; Blamey, Ross C.; Reason, Chris
Abstract: The rainfall mean state and variability of the tropical Southern Hemisphere are strongly affected by the Tropical Convergence Zones. Unlike the South Pacific and South Atlantic, the topography of Madagascar prevents, through the Mozambique Channel Trough, the direct transport of moisture from the Indian Ocean toward southern Africa that feeds the South Indian Ocean Convergence Zone (SICZ). Numerical experiments using regional climate models reveal that a flatter than actual topography over Madagascar results in a strengthening of the SICZ through anomalously high easterly moisture fluxes transported from the Indian Ocean and the Mozambique Channel. These in turn trigger a significant increase in precipitation over southern Africa extending from Mozambique to Angola and a decrease in rainfall over Madagascar. These results have important implications for the improvement of the representation of African rainfall mean state and variability, which has been identified as a persisting issue in different generations of state‐of‐the‐art climate models. Plain Language Summary: We show that the topography of Madagascar is essential to adequately simulate the atmospheric circulation and rainfall over southern Africa and the neighboring southwest Indian Ocean. By conducting a set of numerical experiments, we evaluate the role of Madagascar and its topography in shaping the regional climate. The underlying mechanism through which reduced topography over Madagascar leads to more moisture transported from the Indian Ocean to the African mainland is analyzed. The results also help explain the often observed dipole rainfall anomaly between Madagascar and the mainland and the tendencies for climate models to inadequately represent a realistic mean rainfall pattern over the region. Our results may therefore help in improving the accuracy of models used for seasonal outlooks and climate change projections over Africa. Key Points: The topography of Madagascar modulates the South Indian Ocean Convergence Zone via the Mozambique Channel Trough The strength of the trough strongly influences the amount of moisture transported to southern Africa and hence regulates the precipitation Difficulties models have in simulating southern African rainfall may in part come from inability to represent the topography of Madagascar